Strategies for the Management of Sports Facilities in Schools to Support Sports Activities in Improving Students' Physical and Spiritual Health - Prakoso, Febrian Edo; Setyawan, Trinovandhi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study examines the management of sports facilities in elementary schools and their effects on physical and spiritual health. This descriptive qualitative method's data collection techniques include documentation, interviews, and observation. In the Kedung Kandang District of Malang City, three elementary schools—SDN Bumiayu 1, SDN Lesanpuro 2, and SDN Mergosono 3—provided physical education teachers and students in grades V and VI as research participants. The study's results show that the availability of sports facilities is directly related to the effectiveness of school sports activities. SDN Bumiayu 1 has the highest facility availability (71%) and exhibits the most significant positive impact on student activities, as indicated by indicators such as physical education attendance, enthusiasm, activity diversity, female student participation, and happy expressions after sports. Management strategies that have been successfully implemented include routine maintenance, scheduled use, collaboration with school committees, and utilizing halls as alternative physical activity spaces. This study concludes that a well-managed strategy can maximize the benefits of sports facilities, even under limited conditions, and significantly improve students' physical and mental health. Ongoing support from various parties is needed to create a healthy, active, and inclusive school environment.